Eksplorasi Potensi Alam dan Kuliner Lokal dalam Pengembangan Paket Ekowisata di Desa Tua, Tabanan, Bali - Wulandari, Pande Putu; Bestari, Ni Made Prasiwi; Tirtawati, Ni Made (Jurnal Ilmiah Pariwisata, 2025)
Tua Village in Marga District, Tabanan Regency, holds significant natural and cultural potential for ecotourism development, yet its resources remain underutilized. This study aims to explore and design ecotourism packages that integrate the village’s natural landscape and local culinary heritage to enhance community-based tourism. Using a qualitative descriptive approach, data were collected through interviews, observations, documentation, and desk research. Informants were selected using purposive and snowball sampling, involving local leaders, community elders, and residents near key attractions such as the Bayan Ancient Tree. The findings propose two ecotourism packages, Tabanan Breeze (half-day) and Tabanan Treasures (full-day), which combine cycling tours, rice field experiences, traditional games, and local cooking activities featuring Kaliadrem cake made with Marigold flowers, a primary agricultural commodity in Tua Village. These packages emphasize environmental sustainability, cultural preservation, and local empowerment. The research highlights the importance of ecotourism as a tool to strengthen rural economies, extend tourist stays, and promote Bali’s sustainable tourism development. Keywords: tourism potential, ecotourism, local cuisine, community-based tourism